2011
DOI: 10.1371/journal.pone.0027915
|View full text |Cite
|
Sign up to set email alerts
|

A Flavonoid, Luteolin, Cripples HIV-1 by Abrogation of Tat Function

Abstract: Despite the effectiveness of combination antiretroviral treatment (cART) against HIV-1, evidence indicates that residual infection persists in different cell types. Intensification of cART does not decrease the residual viral load or immune activation. cART restricts the synthesis of infectious virus but does not curtail HIV-1 transcription and translation from either the integrated or unintegrated viral genomes in infected cells. All treated patients with full viral suppression actually have low-level viremia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 75 publications
3
44
0
1
Order By: Relevance
“…RT-PCR for CXCR4, CCR5, CD4 and CD11a transcripts were done as described earlier (Chauhan et al, 2007; Mehla et al, 2011; Mehla et al, 2010) with primer sequnecs (Table S6). In each case, total RNA was extracted from 3–4 × 10 6 cells by Trizol reagent (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-PCR for CXCR4, CCR5, CD4 and CD11a transcripts were done as described earlier (Chauhan et al, 2007; Mehla et al, 2011; Mehla et al, 2010) with primer sequnecs (Table S6). In each case, total RNA was extracted from 3–4 × 10 6 cells by Trizol reagent (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Viral integration in HIV-1-infected astrocytes was monitored by Alu-HIV LTR PCR, as described (Mehla et al, 2011; Vijaykumar et al, 2008). Total DNA was extracted using DNAzol reagent (Invitrogen) and amplified by nested PCR using 1.25 units of platinum Taq polymerase, 0.1 mM dNTP mix, 30 pico-moles of each primer with 1.2 mM Mg 2+ in a 50 μl reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, flavonoids have been shown to show inhibitory effects against viruses including HIV and respiratory syncytial virus (Li et al, 2000). Plant-derived flavonoids have been reported to inhibit critical steps in the life cycle of HIV infectivity such as viral entry (Liu et al, 2011), reverse transcriptase (Li et al, 2011), integrase (Lee et al, 2003;Tewtrakul et al, 2003), viral transcriptional activities of HIV tat (Mehla et al, 2011) and protease inhibitory activities (Lee et al, 2009) and other activities. M. oleifera is also rich in saponins which have been reported to inhibit HIV infectivity, in vitro (Konoshima et al, 1995;Yang et al, 1999;Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For baicalin, computational studies also showed a high binding affinity (-9.8 kcal/mol) against chikungunya virus (CHIKV) nsP3 protein, suggesting that baicalin can potentially interfere with CHIKV infection [114]. It was found that luteolin has antiviral effect on HIV-1 reactivation by blocking both clade B-and C-Tat-driven LTR transactivation [87]. Luteolin also showed significant inhibition of Epstein-Barr virus (EBV) reactivation in cells [133]; it suppressed the activities of the immediate-early genes Zta and Rta by deregulating transcription factor Sp1 binding.…”
Section: Antiviral Activity Of Flavonesmentioning
confidence: 99%